Pengembangan Media Pembelajaran Interaktif Berbasis SAC Materi Adab terhadap Orang Tua dan Guru - Sumardin, A. Putri Amalia; Fakhrunnisaa, Nur; K, Nurdin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study discusses the development of interactive learning media based on Smart Apps Creator (SAC) adab material towards parents and teachers with the aim of knowing the level of student response and the level of product validity. This type of research uses development research with the four D (4D) model, namely define, design, develop, and dissiminate. Data collection techniques are interviews and validation questionnaires. Data analysis techniques are validation questionnaire analysis and student response questionnaire. The results of the research developed by researchers obtained validation results from media experts of 95.25% with a very valid category, as well as material expert validation of 94.75% with a very valid category and student response questionnaire results of 83.42% with a very high category. Based on the results of the study, it can be concluded that the smart apps creator-based interakti learning media is useful for students and is suitable for use as a learning media because it meets the criteria.